Pengembangan Model Pembelajaran Matematika Berbasis Pepro Kreasi Di Madrasah Tsanawiyah - Mutmainah Mutmainah (Jurnal Teknologi Pendidikan)
The development of mathematical learning models based on Pepro Kreasi at junior high boarding school. This study aims to develop instructional mathematics models based on Pepro Kreasi (Knowledge, Processes, Creativity, Activity, and Attitude)that can increase the competencies, interest, and student learning outcomes. In edition to using lesson matter book, as well as using assessment instrument.Development of instructional models followed the Dick & Carey model.this study result the design of instructional, learning resources book that we call Mardhi (mathematics magazine), and the user guide for teacher and student that .Formative test that involved expert testing, one-to-one, small group, and field test, were carried out and resulted in conceptual, procedural, and physical models for the development of viable and effective instructional mathematics models to be used in Al- Ishlahuddiny junior boarding high school. Keywords: mathematic instructional, models, lesson matter, assessment instrument, and pepro kreasi. Tujuan penelitian ini menghasilkan model pembelajaran matematika berbasis Pepro Kreasi (Pengetahuan, Proses, Kreativitas, Aplikasi, dan Sikap) yang dapat meningkatkan kompetensi, minat dan hasil belajar siswa. Selain menggunakan bahan ajar, digunakan juga instrumen penilaian dalam kegiatan pembelajaran. Metode yang digunakan dalam Research and Development adalah model pengembangan Dick & Carey. Hasil penelitian ini adalah desain pembelajaran, bahan ajar yang disebut sebagai Mardhi (majalah Ar-Riyadhiyat), dan buku panduan penggunaan untuk guru dan siswa. Uji coba formatif berupa uji ahli, uji 0ne-to-one, uji kelompok kecil, dan uji lapangan. Penelitian ini menghasilkan model konseptual, prosedural, dan fisikal, yang telah teruji efektivitas, efisiensi dan kelayakannya untuk pembelajaran matematika yang digunakan di madrasah Tsanawiyah Al-Ishlahuddiny. Kata kunci: pembelajaran matematika, model, bahan ajar, instrumen penilaian, pepro kreasi.